2022
DOI: 10.1017/s0950268822000462
|View full text |Cite
|
Sign up to set email alerts
|

Prospective spatial-temporal clusters of COVID-19 in local communities: case study of Kansas City, Missouri, United States

Abstract: Kansas City, Missouri, became one of the major United States hotspots for COVID-19 due to an increase in the rate of positive COVID-19 test results. Despite the large numbers of positive cases in Kansas City, MO, the spatial-temporal analysis of data has been less investigated.However, it is critical to detect emerging clusters of COVID-19 and enforce control and preventive policies within those clusters. We conducted a prospective Poisson spatial-temporal analysis of Kansas City, MO data to detect significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Observe that the statistics of susceptible and recovered data are comparable (see S1 File for the basic descriptive statistics). However, the statistics of infected individuals are at a much [46,47].…”
Section: Datamentioning
confidence: 99%
“…Observe that the statistics of susceptible and recovered data are comparable (see S1 File for the basic descriptive statistics). However, the statistics of infected individuals are at a much [46,47].…”
Section: Datamentioning
confidence: 99%
“…Several other papers have centered on assessing the degree of geographic disparities with regards to COVID-19 risk and have tried to link these disparities to the geographic distribution of cases and/or deaths. Studies of this type have been carried out on the two major urban areas in the state, St. Louis [ 26 , 27 ] and Kansas City [ 28 , 29 ], but no studies dealing with other parts of the state have been identified.…”
Section: Introductionmentioning
confidence: 99%